2007
DOI: 10.1002/pmic.200700572
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of protein N‐glycosylation in 2‐DE: Erythropoietin as a study case

Abstract: The structure, function, and physico-chemical properties of many proteins are determined by PTM, being glycosylation the most complex. This study describes how a combination of typical proteomics methods (2-DE) combines with glycomics strategies (HPLC, MALDI-TOF-MS, exoglycosidases sequencing) to yield comprehensive data about single spot-microheterogeneity, providing meaningful information for the detection of disease markers, pharmaceutical industry, antidoping control, etc. Recombinant erythropoietin and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
42
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 47 publications
7
42
0
Order By: Relevance
“…Many authors have studied the glycosylation features of human and recombinant EPOs in order to distinguish them due to both the misuse of rEPOs among athletes and to the clinical use of these drugs as a treatment for anaemia [16,18,22,23]. Several spots corresponding to rEPOs are resolvable at pIs between 3 and 5, depending on the source [22][23][24][25].…”
Section: State Of the Artmentioning
confidence: 98%
See 3 more Smart Citations
“…Many authors have studied the glycosylation features of human and recombinant EPOs in order to distinguish them due to both the misuse of rEPOs among athletes and to the clinical use of these drugs as a treatment for anaemia [16,18,22,23]. Several spots corresponding to rEPOs are resolvable at pIs between 3 and 5, depending on the source [22][23][24][25].…”
Section: State Of the Artmentioning
confidence: 98%
“…Many authors have studied the glycosylation features of human and recombinant EPOs in order to distinguish them due to both the misuse of rEPOs among athletes and to the clinical use of these drugs as a treatment for anaemia [16,18,22,23]. Several spots corresponding to rEPOs are resolvable at pIs between 3 and 5, depending on the source [22][23][24][25]. Different studies have concluded that the trains of spots observed in 2-DE for EPO (both human and recombinant) are a result of different sialylation patterns of EPO, but none of these studies have obtained a correlation between the pI and the SA content [16,18,22,23].…”
Section: State Of the Artmentioning
confidence: 99%
See 2 more Smart Citations
“…Rapid glycan profiling is possible with few seconds of acquisition times in a high-throughput manner. 4,5,20 Most of EPO N-glycans are multi-antennary glycans having high sialic acid residues, therefore, EPO Nglycans are analyzed in the negative ion detection mode to obtain overall profiling of N-glycan compositions during MALDI-MS. Figure 2a shows representative MALDI-TOF MS spectrum of native N-glycans released from the second generation EPO (NESP). High resolution TOF-MS provided accurate mass, simplifying identification of molecular ion, compositional assignment of each detected glycans.…”
mentioning
confidence: 99%